Influence of Employee Learning on Career Growth: The Mediating Role of Employee Performance among Working Students at Universitas Terbuka - Yulia Zakhiatul Aufa; Mia Ayu Gusti (Manunggal Halim Jaya, 2026)
Rapid technological advancement and changing labor market demands have increased the importance of continuous learning to maintain career growth, particularly among employees pursuing higher education while working. This study investigates the direct effect of employee learning on career growth and examines the mediating role of employee performance in this relationship among working students at Universitas Terbuka. A quantitative approach with a causal research design was employed. The population consisted of active working students at Universitas Terbuka, and a sample of 160 respondents was selected using incidental sampling. Data were collected using a structured questionnaire using a five-point Likert scale. The research instrument was adapted from Yoopetch et al. (2021), comprising six indicators of employee learning, six indicators of employee performance, and four indicators of career growth. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that employee learning has a positive and significant effect on career growth (β = 0.523, p < 0.001) and employee performance (β = 0.692, p < 0.001). Employee performance also has a positive and significant effect on career growth (β = 0.192, p = 0.016) and partially mediates the relationship between employee learning and career growth (indirect effect β = 0.133, p = 0.017; VAF = 20.27%). The findings extend Human Capital Theory by demonstrating that employee performance serves as an important mechanism through which investment in employee learning is translated into career growth. Practically, the study suggests that organizations should strengthen continuous learning initiatives and support employees pursuing higher education, while Universitas Terbuka should continue providing flexible learning systems that enhance students' workplace performance and long-term career development.